Biomineralization behavior of HAp/CNTs/Ti6Al4V into the simulated body fluid solution - Thom, Nguyen Thi; Mai Thanh, Dinh Thi; Thanh Van, Tran Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Hong, Cao Thi; Kieu Anh, Vo Thi (Vietnam Journal of Science and Technology, 2019)
Hydroxyapatite doped carbon nanotubes (HAp/CNTs) was synthesized successfully as a coating on the surface of titanium alloy (Ti6Al4V) by a scanning potential method. The biocompatibility of the materials soaked into a simulated body fluid solution (SBF) were investigated. SEM images are observed that the formation of new apatite crystals on the surface of Ti6Al4V with HAp or HAp/CNTs coating is better than that of Ti6Al4V. The formed apatite crystals are confirmed by XRD result of Ti6Al4V after 21 soaked days in SBF solution. These results indicated that the coatings of HAp or HAp/CNTs have a good biocompatibility.